A concept of geo-facts for online discourse in "Postfactual" times in the context of spatial planning. - Navratil, Gerhard; Harnoncourt, Max (My University, 2018)
The paper discusses geo-facts and their importance in discussions. The context of the examples is spatial planning. It is assumed that geo-facts should be the basis for modern (trustworthy and reliable) e-participation in spatial planning processes. This is discussed in comparison with alternative facts and some ideas about necessary data on facts are presented. Starting from an intuitive definition of facts we develop the concept of geo-facts, show their usefulness for discourse in a spatial planning environment, and points out some technical details. The paper discusses ideas and aims at presenting a vision rather than present a detailed evaluation and solution that is ready to be implemented. The goal of this paper is starting a discussion how expertise can be stored and used.
Keywords: Raumplanung; Geodaten; Fachwissen